Concepts and Practices of Welcoming Ramadhan - Aulia Rizka; Miftahul Ihsan; Alfarizi Owen Satria; Muhammad Abdul Aziz (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
Another aspect of Ramadan that is regulated by Islamic law is the concept and practice of welcoming the month of Ramadhan. This article aims to analyze what the concept and practice of welcoming Ramadhan should be. This article is written using a qualitative method with the type of living Quran and hadith research, the data sources are taken from the Quran and hadith, the results of ijtihad, the opinions of experts. In addition, the author also strengthens data sources from various previous research results that have been published in reputable international journals. All the data above were analyzed thematically using Milles and Huberman's interactive analysis technique. The results of the analysis show that there are eight concepts in welcoming Ramadhan. There are three concepts and six practices in Muslim communities that are ways to welcome the month of Ramadhan. This research can be used as a reference for further research on Islamic studies, encourage public awareness that the blessing of Ramadhan is more important than just carrying out traditions that do not necessarily bring blessings and become a guide for Muslims in welcoming Ramadhan as a special month in a special way.